Cabo Verde : Request for an Arrangement Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Cabo Verde. (IMF Staff Country Reports; Country Report ;, 2022)
Cabo Verde's economy is facing significant economic challenges associated with the lingering effects of the pandemic, as well as rising food and fuel prices triggered by the war in Ukraine. Climate change is also creating new difficulties after a fourth consecutive drought year. The economy rebounded strongly in 2021 following the COVID-19 induced recession in 2020, due in part to the authorities' effective policy response, including one of the most successful vaccination programs in sub-Saharan Africa. However, the spillover effects of the Ukraine war are likely to weaken the economic recovery, worsen the fiscal and external positions, lead to higher inflation, and result in a substantial decline in international reserves. As a result, strong policy measures are needed to shore up international reserves, preserve debt sustainability, increase resilience to shocks, including climate change adaptation and mitigation, and make growth more inclusive.